DETERMINAN FAKTOR PENENTU PEMBAYARAN DIVIDEN DENGAN GROWTH OPPORTUNITY DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 – 2017) - Indriyani, Sari; Djaddang, Syahril; Syam, Ardiansyah (SEKOLAH PASCASARJANA PRESS, 2021)
The objective of this research is to analyze the effect of capital structure, collateral assets, business risk, Return On Equity (ROE) on determinants of dividend payments (DPR) with growth opportunity and firm size as moderating. The object of this research is all companies listed on the Stock Exchange (BEI) in 2014-2017. The sampling method used was purposive sampling with quantitative secondary data. The method of data analysis is Structural Equation Modeling Partial Least Square (SEM-PLS) using WarpPLS 6.0 program. The results are capital structure, collateral assets, business risk, and growth opportunity are significant effect on determinants of dividend payments (DPR), Return On Equity (ROE) has negative effect on determinants of dividend payments (DPR), while firm size has no significant effect on determinants of dividend payments (DPR). Growth opportunity strengthens of relationship between collateral assets and business risk to determinants of dividend payments (DPR). And firm size strengthens of relationship between collateral assets and business risk to determinants of dividend payments (DPR).